PENERAPAN PEMOTONGAN, PENYETORAN, DAN PELAPORAN PPH FINAL ATAS JASA KONSTRUKSI e-SPT MASA 2017 - Daniela Anauskah (Universitas Medan Area, 2018)
This study aims to assist the company in applying Cutting, Depositing, and Reporting Income Tax Article 4 paragraph (2) for construction services by WIKA-HUTAMA JO Belawan Phase 2 e-SPT Period 2017. The period of this study starts from July to September. In this research the researcher use primary data type and secondary data, internal data source, action research type, interview data collecting technique, documentation and library research, and descriptive data analysis method with qualitative approach. Based on the results of the study, Implementation of Cutting, Depositing, and Reporting Income Tax Article 4 paragraph (2) on Construction Services by WIKA-HUTAMA JO Belawan Phase 2 e-SPT 2017 is in accordance with the provisions of taxation Income Tax Law. 36 Year 2008. WIKA-HUTAMA JO impose tax rate in accordance with the provisions of applicable tax rates. Then WIKA-HUTAMA JO creates a list of proof of deduction and fills correctly and complete evidence of withholding of Income Tax Article 4 Paragraph (2) of Construction Services in accordance with the forms and fields specified by the Director General of Taxes. Deposit of Income Tax Article 4 Paragraph (2) of the Construction Service shall be made before the deadline of the withholding of income tax to the state treasury. Reporting of Income Tax Article 4 Paragraph (2) for Construction Services shall also be made before the deadline for reporting the Income Tax Article 4 Paragraph (2) to the Tax Office.